EFEK INDOOR AIR POLLUTION TERHADAP KESEHATAN - Aurora, Wahyu Indah Dewi (Scientific Of Environmental Health and Diseases, 2021)
ABSTRACT In recent decades, indoor air quality has been of particular concern because of its contribution to health. It is estimated that as much as 90% of people spend their time indoors rather than outdoors. If the ventilation system is poor, it will result in an accumulation of pollutants in the room. These pollutants can come from outdoor air that enters the room, growing microorganisms, interior furniture or furniture or from the daily activities of humans themselves. The health problems that will be caused also vary. It can be from lung disease caused by inhalation of dangerous pollutants such as lung infections, pneumonia, asthma or COPD. Or other diseases such as Sick Building Syndrome, nasopharyngeal cancer, skin irritation, eye irritation, etc. To overcome this, careful planning is needed when building a room or building to minimize health problems due to indoor air, one of which is collaborating with several experts. Keywords: Indoor Air Quality, Indoor Air Pollution, Health disease ABSTRAK Dalam beberapa decade terakhir,kualitas udara dalam ruangan menjadi perhatian khusus karena kontribusinya pada segi kesehatan. Diperkirakan ada sebanyak 90% orang-orang menghabiskan waktunya di dalam ruangan daripada di luar ruangan. Jika system ventilasi buruk, maka akan menghasilkan akumulasi polutan yang ada dalam ruangan. Polutan tersebut bisa berasal dari udara luar ruangan yang masuk ke dalam ruangan, mikroorganise yang tumbuh, perabotan atau furniture interior ruangan ataupun dari aktivitas keseharian manusia itu sendiri. Gangguan kesehatan yang akan diakibatkan pun bermacam-macam. Bisa dari penyakit paru akibat terhirup polutan yang berbahaya seperti penyakit infeksi paru, pneumonia, asma atau PPOK. Atau penyakit lain seperti Sick Building Syndrome, kanker nasofaring, iritasi kulit, iritasi pada mata, dll. Untuk mengatasinya perlulah perencanaan yang matang pada saat pembangunan sebuah ruangan atau gedung untuk meminimalisir gangguan kesehatan akibat udara dalam ruangan, salah satunya adalah berkolaborasi dengan beberapa ahli. Keywords: Indoor Air Quality, Indoor Air Pollution, Health disease